Characterization of Powder River Basin coal pyrolysis with cost-effective and environmentally-friendly composite NaFe catalysts in a thermogravimetric analyzer and a fixed-bed reactor. (5th April 2018) - Xu, Bang; Kuang, Dongyang; Liu, Fangjing; Lu, Wenyang; Goroncy, Alexander K.; He, Ting; Gasem, Khaled; Fan, Maohong
Abstract: The pyrolysis characteristics of PRB coal with use of NaFe composite catalysts were investigated in a thermogravimetric analyzer and a fixed bed reactor. Model-free methods developed by Friedman (FR), Kissinger-Akahira-Sunose (KAS), Flynn-Wall-Ozawa (FWO) and Vyazovkin (VA) were compared and applied to determine the pyrolysis kinetic parameters. A Master-plot method was used to determine the reaction order and pre-exponential factors. Raw coal with the addition of 4% FeCO3 achieved the highest effect on coal conversion; specifically, 4% Na2 CO3 and 1% Na2 CO3 –3% FeCO3 showed higher effect than 3% Na2 CO3 –1% FeCO3 and 2% Na2 CO3 –2% FeCO3 . The averaged E values of raw coal with 4% FeCO3 catalyst decreased by 10% compared with that of raw coal. Compared with the individual use of 4% Na2 CO3, the addition of FeCO3 can be effective in decreasing the E values of the raw coal. The nonlinear VA method appears to be superior in determining activation energies of coal pyrolysis at considered conversion range. Further, the An (random nucleation and nuclei growth model) appears to be the appropriate reaction model for raw coal pyrolysis with and without the use of NaFe composite catalysts. From the pyrolysis in the fixed bed reactor, XRD and FTIR tests for coal chars produced by PRB coal pyrolysis with use of catalysts were conducted. By combining the gas evolution and XRD/FTIR results, a reaction mechanism is proposed for coal pyrolysis with composite Na2 CO3 FeCO3 catalysts. Graphical abstract: Highlights: Catalytic pyrolysis kinetic characteristics of PRB coal were studied. Model free and master-plots methods were used. Composite NaFe catalysts can lower activation energy. Pyrolysis mechanism of PRB coal with NaFe catalysts was proposed.